PROTEIN MARKERS OF THE HYPOXIC-ISCHEMIC INJURY OF THE CENTRAL NERVOUS SYSTEM IN THE PERINATAL PERIOD - D. V. Blinov (Акушерство, гинекология и репродукция, 2016)
Preeclampsia (gestosis) and eclampsia, as well as the acute intranatal hypoxy often act as trigger for the development of the perinatal hypoxic-ischemic brain injury. That is accompanied by such typical structural changes as periventricular leukomalacia (PVL) and intraventricular hemorrhages (IVH). The hypoxic-ischemic brain injury in the perinatal period can have such consequences as hydrocephaly, microcephaly, infantile cerebral paralysis (ICP), epilepsy and motormental retardation. It is not always possible to determine the disease gravity and forecast of the disease by routine methods of clinical, instrumental and laboratory examination. As it is proved, that the perinatal hypoxic-ischemic brain injury is always accompanied by the disruption of Blood-Brain-Barrier (BBB) permeability for neuron-specific proteins (NSP). NSP can be considered as markers of this pathologic process. Nowadays there are more or less details on 120 NSP, namely, non-enzyme neurospecific Са+ -binding proteins; non-enzyme NSP, responsible for adhesion and intercellular recognition processes; соntractile and cytoskeletal nervous tissue proteins; secreted regulatory and transport NSP; myeline proteins and glial NSP. To evaluate BBB status it is expedient to select from the variety of known NSP most studied proteins, being neurons’ and astrocytes’ markers. Such NSP are gliofibrillary acid protein, GFAP and neuronspecific enolase, NSE. In normal conditions the NSP are within BBB and can be almost undeterminable in the blood serum. In case of the BBB permeability disruption NSP penetrate to the peripheral blood flow and can be determined. The dynamic determination of the NSP in the blood serum can be expedient to evaluate the BBB resistance, to determine the degree of the CNS injury and the disease state forecast at children with perinatal hypoxic-ischemic brain injury.